(untitled) (Green University Review of Social Sciences, 2022)
This paper is an attempt to scrutinize the impact of EMI policy (English as a Medium of Instruction) on the academic result of the students of a renowned private university in Bangladesh, based on the teachers’ and students’ perceptions. After passing twelve years of education in Bengali medium instruction, when the students get themselves admitted into different private universities, they are confronted with EMI policy in their academic contexts. In most of the cases, it has been observed that the MOI (medium of instruction) used in classrooms is purely English. This may raise the affective filter of the freshers, coming from Bengali medium schools and colleges, leading towards gaining poor grades in their academic results. Hence, this research attempts to find out whether there is an association between the poor examination results and EMI policy according to the teachers’ and students’ perspectives. However, the research findings expose that the majority of the students encounter problems to upgrade their academic results because of using EMI strictly both in classrooms and in examinations. In addition, some teachers pointed out, due to EMI policy students face some problems initially, but there is no other way than accepting EMI /English as a medium of instruction to make the students adapted with the globalized world. On the other hand, a great number of the teachers think that a bilingual medium of instruction actually helps the students to study with interest and motivation, and to have a sound grasp over the content. Green University Review of Social Sciences Dec 2021; 7(1-2): 89-104